2019
DOI: 10.1007/s00268-019-05248-9
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology, Presentation and Management of Ischaemic Colitis: A Systematic Review

Abstract: There are currently no guidelines on the long-term management of patients after an episode of acute ischaemic colitis. Our aim was to review the literature on the pattern of presentation and the pathophysiology of this condition and to understand the current status of the acute and long-term management of ischaemic colitis. Furthermore, we aim to provide recommendations for the clinicians in regard to the acute and long-term management of ischaemic colitis. A review of the English literature over the last 15 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
(251 reference statements)
1
17
0
Order By: Relevance
“…The results of this study reinforce the fact that the incidence of colonic ischemia is higher in female patients than in male patients, and IC is more common among older patients, as previously reported [ 8 , 13 ]. This might be attributed to older patients’ increased susceptibility to atherosclerosis, which is one of the postmenopausal changes that leads to alterations in the blood supply of the colon, with a great impact on the areas of the colon most vulnerable to ischemic insult [ 14 ]. Previous studies indicated that abdominal pain, hematochezia, and diarrhea are the most common symptoms of IC, which is nearly consistent with the results of our study, as abdominal pain and rectal bleeding were the most frequent symptoms at presentation, followed by decreased appetite, abdominal distension, and diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study reinforce the fact that the incidence of colonic ischemia is higher in female patients than in male patients, and IC is more common among older patients, as previously reported [ 8 , 13 ]. This might be attributed to older patients’ increased susceptibility to atherosclerosis, which is one of the postmenopausal changes that leads to alterations in the blood supply of the colon, with a great impact on the areas of the colon most vulnerable to ischemic insult [ 14 ]. Previous studies indicated that abdominal pain, hematochezia, and diarrhea are the most common symptoms of IC, which is nearly consistent with the results of our study, as abdominal pain and rectal bleeding were the most frequent symptoms at presentation, followed by decreased appetite, abdominal distension, and diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the clinical findings, patients can present abdominal tenderness, and, in severe cases, signs of acute peritonitis (abdominal distension, guarding and severe tenderness) 17 . Therefore, the triade formed by abdominal pain, tenderness and rectal bleeding represents the main presentation form 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rate is considered around 15% 8 . Studies have shown that right colon ischemia or involvement of both right and left colon in patients with age over 50 years are associated with poor outcome 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic colitis (IC) is a severe emergency in gastrointestinal surgery [1], being associated with mortality rates of 50-80% [2,3]. IC represents the most common type of intestinal ischemia with an estimated incidence of 15.6-17.7/100,000 person-years [4].…”
Section: Introductionmentioning
confidence: 99%